Clinical Manifestations and Molecular Diagnosis of Scrub Typhus and Murine Typhus, Vietnam, 2015–2017 - Trung, NV; Hoi, LT; Dien, VM; Huong, DT; Hoa, TM; Lien, VN; Van Luan, P; Lewycka, SO; Choisy, M; Bryant, JE; Nadjm, B; van Doorn, H; et al. (Centers for Disease Control and Prevention, 2019)
Rickettsioses are endemic to Vietnam; however, only a limited number of clinical studies have been performed on these vectorborne bacteria. We conducted a prospective hospital-based study at 2 national referral hospitals in Hanoi to describe the clinical characteristics of scrub typhus and murine typhus in northern Vietnam and to assess the diagnostic applicability of quantitative real-time PCR assays to diagnose rickettsial diseases. We enrolled 302 patients with acute undifferentiated fever and clinically suspected rickettsiosis during March 2015-March 2017. We used a standardized case report form to collect clinical information and laboratory results at the time of admission and during treatment. We confirmed scrub typhus in 103 (34.1%) patients and murine typhus in 12 (3.3%) patients. These results highlight the need for increased emphasis on training for healthcare providers for earlier recognition, prevention, and treatment of rickettsial diseases in Vietnam.